Evaluación de las características de los ovocitos en cerdas de camal según condición corporal 2 3 y 4 - Manjarrés Frías, Oscar Eucebio (2015)
The main objective of this research was to evaluate the characteristics of the oocyte according to body condition bristle of slaughterhouse through a CEYPSA biotechnology of reproduction laboratory to demonstrate its functionality. Bristles from slaughterhouse ovaries collected in the slaughterhouse of Ambato were collected for this purpose, the procedure was carried out with 30 ovaries according to body condition, which were classified into three groups, G1 (CC2), G2 (3 CC), G3 (CC4). Was obtained 218 oocytes equivalent to 100% of the three groups, which will I qualify according to their quality in categories, obtaining 157 oocytes of category I, representing 72,02%, 28 oocytes from category II, representing 12.844%, and 33 oocytes from category III, representing 15.14%....